Histone deacetylases 1 and 2 redundantly regulate cardiac morphogenesis, growth, and contractility - Montgomery, Rusty L. (Cold Spring Harbor Laboratory Press, 2007)
Histone deacetylases (HDACs) tighten chromatin structure and repress gene expression through the removal of acetyl groups from histone tails. The class I HDACs, HDAC1 and HDAC2, are expressed ubiquitously, but their potential roles in tissue-specific gene expression and organogenesis have not been defined. To explore the functions of HDAC1 and HDAC2 in vivo, we generated mice with conditional null alleles of both genes. Whereas global deletion of HDAC1 results in death by embryonic day 9.5, mice lacking HDAC2 survive until the perinatal period, when they succumb to a spectrum of cardiac defects, including obliteration of the lumen of the right ventricle, excessive hyperplasia and apoptosis of cardiomyocytes, and bradycardia. Cardiac-specific deletion of either HDAC1 or HDAC2 does not evoke a phenotype, whereas cardiac-specific deletion of both genes results in neonatal lethality, accompanied by cardiac arrhythmias, dilated cardiomyopathy, and up-regulation of genes encoding skeletal muscle-specific contractile proteins and calcium channels. Our results reveal cell-autonomous and non-cell-autonomous functions for HDAC1 and HDAC2 in the control of myocardial growth, morphogenesis, and contractility, which reflect partially redundant roles of these enzymes in tissue-specific transcriptional repression.